Number of functional teeth more strongly predicts all‐cause mortality than number of present teeth in Japanese older adults. Issue 6 (29th March 2020) - Maekawa, Kenji; Ikeuchi, Tomoko; Shinkai, Shoji; Hirano, Hirohiko; Ryu, Masahiro; Tamaki, Katsushi; Yatani, Hirofumi; Kuboki, Takuo; ,; Kimura‐Ono, Aya; Kikutani, Takeshi; Suganuma, Takashi; et al.
Abstract : Aim: Previous studies on the association between intraoral conditions and mortality in community‐dwelling older individuals reported that fewer present teeth (PT) are significant risk factors for mortality. However, how the number of PT relative to the number of functional teeth (FT), including both present and rehabilitated teeth, influences mortality has not been investigated fully. This study examined the impact of the number of FT on mortality among community‐dwelling Japanese older adults. Methods: This study was a retrospective, observational and population‐based follow‐up study, which examined 1188 older individuals who participated in an annual geriatric health examination from 2009 to 2015. The average follow‐up period was 1697.0 ± 774.5 days. The primary outcome was all‐cause mortality at follow‐up. The numbers of PT and FT of each participant were counted during an oral examination. In addition, demographics, clinical variables, blood nutrient markers, physical functions and perceived masticatory function were measured. Results: Kaplan–Meier analysis, followed by a log‐rank test, revealed that fewer PT ( P  < 0.001) and FT ( P = 0.002) were significantly associated with a reduced survival rate. Cox's proportional hazard analysis indicated that the number of FT, but not the number of PT, was a significant independent mortality risk factor after adjusting for demographics, clinical variables, nutrient markers and physical functioning ( P = 0.036, hazard ratio: 2.089). Conclusions: Current results suggest that the number of FT more strongly predicts all‐cause mortality than the number of PT among community‐dwelling older adults. Further studies are necessary to consider the confounding of socioeconomic status and disability status. Geriatr Gerontol Int 2020; : – .